The development and origin of the two-stage silicification of Upper Jurassic limestones from the northern part of the Kraków-Częstochowa Upland (Southern Poland) - Kochman, Alicja; Matyszkiewicz, Jacek (Geology, Geophysics and Environment, 2023)
The Upper Jurassic carbonates representing the microbial-sponge megafacies in the area of the Kraków-Częstochowa Upland (KCU) were locally silicified. In the reclaimed Lipówki Quarry, in Rudniki near Częstochowa (in the northern part of the Upland), macroscopically different silicification products were observed in blocks of Upper Jurassic limestones, deposited as mining waste. Two varieties were distinguished: (i) chert concretions representing the I silicification stage and (ii) light-brown, silicified limestones infilling the fractures in chert concretions or forming the cortices around the concretions or forming irregular bodies, all representing the II silicification stage. The diagnostic features are the following: (i) macroscopic development, (ii) the presence of moganite exclusively in chert concretions and (iii) significant differences in crystallinity index (CI) values, namely: 0.1–0.7 for chert concretions and 6.0–6.6 for silicified limestones. The formation of chert concretions was initiated as early as in unconsolidated sediment, whereas the II silicification stage followed the chemical compaction of the limestones. The results of geochemical analyses of the products of both silicification stages indicated that the probable source of silica were the low-temperature hydrothermal solutions. Two types of fractures were found in the chert concretions, generated during different tectonic events. The older, open fractures were formed during the extension of the Late Jurassic sedimentary basin, which formerly occupied the territory of the more recent KCU. These fractures were infilled with unconsolidated, fine-detrital carbonate sediment, in which the concretions were embedded and finally silicified in the II silicification stage. The younger, closed fractures, transversal to those filled by the products of II silicification stage, along which small displacements are evident, document the later tectonic deformations presumably related to Cenozoic faulting.